The problematic character in Bakhtiar Ali's novel (Ewaray Parwana (Raparin Journal of Humanities (RJH), 2024)
One of Lucien Goldmann's inventions is the problematic character who disagrees with the globalized and capitalist world, seeks high values, and strives to achieve them, but is lost or murdered. In this investigation, entitled “The problematic character in Bakhtiar Ali's novel Ewaray Parwana”, we want to present the reflection of such a character in “Ewaray Parwana” and open another entryway to the relationship between literature and society based on Goldmann’s problematic character. For this, we have first presented the issue of the relationship between literature and society, and then explained the principle of “problematic character” in the view of Goldmann and thus organizing the theoretical outline of our research. Later, an attempt has been made to identify the details of the character's appearance in the novel.Our research hypothesis is that the problematic character very clearly exists in “Ewaray Parwana”, which reflects the new situation in Kurdish society. To reach the truth of this hypothesis, we have tried to apply the principle of the problematic character to the novel with an analytical descriptive method. In the last part, we have reached some conclusions; can be pointed out that there is a problematic character in the novel and the reason for this is the strangeness and discomfort of the characters with the complexities of life and common social relationships.